On AI. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2023)
"If you read nothing else on artificial intelligence and machine learning, read these 10 articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you understand what's happening, look ahead to what's possible, and bring your AI efforts to scale. This book will inspire you to: develop your next AI strategy; seize the potential of natural language processing; prepare for jobs and industries to be transformed; help people and machines work together; prepare for the regulation of AI; develop algorithms for sales and marketing; stop tinkering with AI and go all in"--
Competing in the age of AI / by Marco Iansiti and Karim R. Lakhani -- How to win with machine learning / by Ajay Agrawal, Joshua Gans, and Avi Goldfarb -- Developing a digital mindset / by Tsedal Neeley and Paul Leonardi -- Learning to work with intelligent machines / by Matt Beane -- Getting AI to scale / by Tim Fountaine, Brian McCarthy, and Tamim Saleh -- Why you aren't getting more from your marketing AI / by Eva Ascara, Michael Ross, and Bruce G.S. Hardie -- The pitfalls of pricing algorithms / by Marco Bertini and Oded Koenigsberg -- A smarter strategy for using robots / by Ben Armstrong and Julie Shah -- Why you need an ai ethics committee / by Reid Blackman -- Robots need us more than we need them / by H. James Wilson and Paul R. Daugherty -- Stop tinkering with AI / by Thomas H. Davenport and Nitin Mittal -- ChatGPT is a tipping point for AI / by Ethan Mollick.
Includes index.
Description based on online resource; title from digital title page (ProQuest Ebook Central, viewed March 7, 2024).
WorldCat record variable field(s) change: 050
Keywords: Industrial management -- Data processing; Artificial intelligence; Robots, Industrial; Gestion -- Informatique; Intelligence artificielle; Robots industriels; artificial intelligence; Artificial intelligence; Industrial management -- Data processing; Robots, Industrial